A Lesson to Scientists from the Prophet Ibrahim’s (Alayhi As-Salam) Miracle of “The fire that does not burn” - ÇAKSEN, HÜSEYIN (Pakistan Journal of Medical & Health Sciences, 2025)
Death by burning (also known as immolation) is an execution, murder, or suicide method involving combustion or exposure to extreme heat. It has a long history as a form of public capital punishment, and many societies have employed it as a punishment for and warning against crimes such as treason, heresy, and witchcraft. The best-known execution of this type is burning at the stake, where the condemned is bound to a large wooden stake and a fire lit beneath1. Burning at the stake practiced in Babylonia and ancient Israel and later adopted in Europe and North America. In England, the burning of heretics ended in 1612 with the death of Edward Wightman; the country’s last execution for heresy (by hanging) occurred in 1697. Burning at the stake for crimes other than heresy continued into the 18th century2. Currently, although self-immolation is seen in many parts around the world3-5, immolation is particularly common in India6. According to the World Health Organization, around 11 million people suffer from burns every year, and 180,000 die from them. A burn is a condition in which heat, chemical substances, electrical current or other factors cause tissue damage. Burns mainly affect the skin, but can also affect deeper tissues such as bones or muscles7. The Prophet Ibrahim (Alayhi As-Salam [AS]) is accepted as the greatest ancestor by Judaism, Christianity and Islam. Ibrahim (AS) invited his tribe and the Babylonian ruler Nemrud to the religion of Allah, but they did not accept this invitation. He argued with Nemrud, who claimed divinity, but Nemrud was defeated by the evidence presented by Ibrahim (AS). Then, Ibrahim (AS) was thrown into a fire burning so big and so strong with a catapult by Nemrud. However, he miraculously survived the fire. The fire did not burn Ibrahim (AS) as a miracle, with Allah's permission, and the place where he fell turned into a rose garden8. Here, we discuss the Prophet Ibrahim’s (AS), miracle of “the fire that does not burn,” which contains some lessons for today's people including scientists, to draw attention to the importance of the prophets’ stories in the Quran. One-hundred and twenty-four thousand prophets came from the first Prophet Adam (AS), the first man, to the last Prophet Muhammad (Sallallahu Alayhi Wa Sallam)9. Historical events and lives of the prophets have been described through stories in the Holy Books so that people take lessons. There are more than one hundred stories in the Quran. One of the stories is about the Prophet Ibrahim (AS). The miracle of Ibrahim’s (AS) “the fire that does not burn” is described in detail in Surah Al-Anbiya of the Quran10. Bediüzzaman Said Nursi11, the author of the Risale-i Nur Collection12, noted three subtle indications in the ayat 69 of surah Al-Anbiya (We said: “O fire! Be cool and a means of safety for Ibrahim), which is about Ibrahim’s (AS) miracle as follows: The first: Like other natural causes, fire does not act according to its own wishes and nature, blindly, but performs a duty under a command. Thus it did not burn Ibrahim (AS), because it was commanded not to burn him13. The second: There is a degree of heat which burns through its coldness. That is, it has an effect like burning. Through the word, Be cool!, (One Quranic commentary [tafsir] states: If He had not said: Be cool!, it would have burnt him with its coldness) Almighty Allah is saying to the coldness: “Do not burn him with your coldness, the same as your heat!” That is to say, through its coldness, fire at that degree has an effect like burning. It is both fire and cold. In fact, in natural science there is a degree of fire, the state of “white heat,” the heat of which does not spread to its surroundings. It attracts the heat around it to itself and with this cold, freezes surrounding liquids such as water, in effect burning them through its cold. Thus, intense cold is a category of fire which burns through its cold. In which case, this intense cold is surely a part of Hell, for it contains all the degrees and sorts of fire13. The third: Just as there is an immaterial substance like belief which counters the effects of Hell-fire and affords protection against it, the armor of Islam, so there is a physical substance which protects against the effects of worldly fire. For as is required by the Name of All-Wise, this world is the abode of wisdom, and Almighty Allah carries out His works under the veil of causes. Therefore, the fire burnt neither Ibrahim’s body, nor his garments; He imbued them with a state which resisted fire. Thus, by this allusion, the ayat is in effect saying: “O nation of Ibrahim! Resemble Ibrahim, so that your garments may be your armor against fire, your greatest enemy both here and there. Clothe your spirit in belief in Allah, and it will be your armor against Hell-fire. Moreover, there are certain substances which Almighty Allah has hidden in the earth for you which will protect you from the evils of fire. Search for them, extract them, and clothe yourselves in them!” Thus, one of man’s important discoveries and a step in his progress was his finding a substance which fire does not burn; and he clothed himself in garments resistant to fire. So see how elevated, subtle, and fine a garment this ayat weaves on the loom of Hanifan Musliman, which will not be rent in all eternity13. Nomex is an inherently flame-retardant fabric having a meta-aramid chemistry and is predominantly used in military clothing systems to provide protection from intense heat and flame. Nomex has good thermal stability and does not melt with the fiber decomposing between 370-430 °C. When exposed to high heat fluxes, the Nomex fiber consolidates and thickens thus preventing exposure of skin to the incident heat flux and hence second and third degree skin burns14. DuPont was introduced commercially as papers and fibers in 1961. The trademark Nomex nylon was adopted in 196315. Also, polybenzimidazole fibers offer improved flame resistance and retain its strength and flexibility after exposure to flame16. Recently, it was found that the blend of Nomex and carbon fibers showed the best flame resistance performance having a minor char length, minimum weight loss and no after-glow time17. Although Nomex was found in the 20th century, the Quran pointed out over 1,400 years ago that there is a non-combustible and protective substance against fire. The limit drawn and the target indicated of the ayat are much broader and higher than the current technology. The ayat encourages scientists to discover fabric that are resistant to temperature of up to 1,000 °C and even higher, because maximum flame temperature (in air, diffusion flame) of a wood-fired in which Ibrahim (AS) was thrown is 1,027 °C18. Furthermore, although Ibrahim (AS) was thrown from the catapult set up on a very high hill, he had no traumatic brain injury, injury to the abdominal or thoracic cavities, fractures or complex soft tissue injury with Allah's protection. So the ayat also encourages scientists to discover a fabric that has protective properties against both flame and high-energy trauma. In conclusion, the prophets’ lives have been described through stories in the Holy Books so that people including scientists take lessons. The Quran orders people to be like Ibrahim (AS): Put on the fireproof material shirt and clothe your soul with faith. They protect you from the evil of your greatest enemy, fire, both in this world and in the hereafter. Second, the Quran pointed out over 1,400 years ago that there is a non-combustible and protective substance against fire with the miracle of Ibrahim’s (AS) “the fire that does not burn.” Moreover, the Quran shows scientists goals that are more advanced than today's technology and encourages them to do scientific studies.